Clinical study on the safety and efficacy of remimazolam in hysteroscopic surgery under general anesthesia in elderly patients - Xie, Manjie; Zeng, Fanrui; Tian, Qiao; Deng, Huiwei; Tao, Shanqing (Frontiers in Medicine, 2024)
Objective: To evaluate the safety and efficacy of remimazolam in hysteroscopic surgery in elderly patients.Methods: Following hysteroscopic surgery under selected general anesthesia, 60 elderly patients ASA(American Society of Anesthesiologists)class II-III,>65years old were randomly assigned to one of two groups: the R group (remimazolam) or the C group (propofol), each with 30 patients. Sufentanil 0.1μg/kg was given 5 minutes before the operation, remimazolam 0.2mg/kg intravenously in Group R, then 0.5~1mg/(kg.h) by pump, propofol 2mg/kg intravenously in group B, and then 4~8mg/(kg.h) by pump. Maintain BIS (Bispectral index) 40~70, add remimazolam 0.05mg/kg or propofol 0.5mg/kg when the patient is in motion, and stop the administration at the end of the operation. Record the patients' HR, MAP, RR, SpO2, PETCO2, and BIS values at entry (T0), before induction administration(T1), 1 minute after administration(T2), 5 minutes after administration(T3), when stopping administration(T4), when awakening(T5), and 1 minute after awakening(T6), as well as the onset time after administration, the awakening time, the success rate of sedation, and the number and dose of additional medications. Reactions are adverse (hypotension, hypertension, respiratory depression incidence, injection pain, nausea and vomiting following surgery, etc.).The two groups' respective anesthetic success rates were comparable overall.In addition to having a higher BIS value and more extra medications than group C, group R experienced less incidence of respiratory depression, injection pain, and intraoperative hypotension.Remimazolam, which is equivalent to propofol in terms of safety and efficacy for older patients undergoing hysteroscopic surgery, should be further promoted and used.